2009
DOI: 10.1177/193229680900300517
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Lancing Devices for Self-Monitoring of Blood Glucose regarding Lancing Pain

Abstract: We found significant differences in lancing pain between lancing devices. Diabetes patients clearly preferred lancing devices that cause less lancing pain. In order to improve patient compliance with respect to an adequate glycemic control, the medical staff should preferentially prescribe lancing devices that cause less lancing pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 12 publications
0
34
0
Order By: Relevance
“…Given the elasticity of the skin, the minor and transient nature of the wound, and the natural tendency of skin to immediately close after lancing, it is challenging to achieve a blood drop on the skin (regardless of depth) without some postlancing technique to encourage blood to the surface. [19][20][21][22] Following each lancing event, each patient scored his or her perceived pain using the Gracely pain scale. The results indicated that there was no direct relationship between the blood volume collected and pain, with less than 0.01% of the data variance attributed to this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Given the elasticity of the skin, the minor and transient nature of the wound, and the natural tendency of skin to immediately close after lancing, it is challenging to achieve a blood drop on the skin (regardless of depth) without some postlancing technique to encourage blood to the surface. [19][20][21][22] Following each lancing event, each patient scored his or her perceived pain using the Gracely pain scale. The results indicated that there was no direct relationship between the blood volume collected and pain, with less than 0.01% of the data variance attributed to this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…A few head-to-head studies have been performed comparing different lancing devices, showing considerable differences in pain. [5][6][7][8][9] Interestingly, no systematic review about lancing has ever been published, which is in sharp contrast to the considerable number of reviews about SMBG in general.…”
Section: Diagnostic Companiesmentioning
confidence: 71%
“…Lancing pain is determined by several factors: depth of penetration, speed of penetration, overall lancet trajectory, lancet geometry, skin surface, skin fixation, 5 and anatomic location on the finger tip. Considerable progress with regards to lancet quality has been achieved by most manufacturers i.e., better precision of holding specifications, tip quality, effective polishing, and coating for smooth gliding motion into the skin.…”
Section: How To Reduce Pain?mentioning
confidence: 99%
“…88 Problem solving techniques 15 and motivational interviewing are useful strategies to increase adherence with SMBG. 89 Minimizing pain with alternative lancing devices, 90 alternative site testing, 91,92 or flash glucose monitoring systems, 93 may encourage testing. Encouraging patients to view results as "high" rather than "bad" increases testing frequency and improves HbA1c in adults and young people.…”
Section: Addressing Barriers To Technology Use and Strategies To Optimentioning
confidence: 99%